Percutaneous closure of patent ductus arteriosus with the Nit-Occlud® patent ductus arteriosus device in 268 consecutive cases - Andrii V Maksymenko; Yulia L Kuzmenko; Arkadii A Dovhaliuk; Oleksandra O Motrechko; Florian E Herrmann; Nikolaus A Haas; Anja Lehner (Wolters Kluwer Medknow Publications, 2019)
Background: The pfm Nit-Occlud® patent ductus arteriosus (PDA) device is well established for interventional closure of PDA. However, there are still limited data concerning its efficacy and follow-up in larger patient groups. Aims: This study aimed to evaluate the safety and efficacy of the Nit-Occlud® PDA device, implanted both through transpulmonary and transaortic approach, in a large cohort. Methods: From July 2008 to December 2015, 268 consecutive patients were admitted for transcatheter closure of a PDA and were treated with the Nit-Occlud® coil. Clinical, echocardiographic, and angiographic data were evaluated. Results: The median age was 5.2 years (range, 5 months to 62 years), and the median weight was 19.3 kg (range: 5.5-97 kg). Ten (3.7%) patients had weight <10 kg. The most common ductus types treated were Krichenko Type E and A (44.0% and 33.2%, respectively). Twelve (4.5%) patients were treated for residual shunting after surgical PDA closure. The median diameter at the narrowest point was 1.5 mm (range: 0.4-4 mm), the median size of the ampulla was 5 mm (range: 1-15 mm), and the median length was 9 mm (range: 2-25 mm). Device implantation could be successfully achieved in all cases. Closure rates documented immediately after the procedure, at 3-10 days, 1 month, and 6 months after intervention were 62%, 95.1%, 97.8%, and 98.5%, respectively. With the exception of one minor thromboembolic event, there were no procedure-related complications. Conclusion: Closure of PDA with various anatomic variations and sizes can be performed effectively and safely using the Nit-Occlud® coil.